Model Supervisi Berbasis CIPP untuk Penguatan Layanan Bimbingan dan Konseling di Sekolah: Sebuah Systematic Literature Review - Widya Ayu Marliana; Awaliya Awaliya; Ernest Ceti Septyanti; Binti Isrofin (Scidacplus, 2026)
Effective supervision of guidance and counseling (BK) is a key factor in ensuring accountability and improving the quality of BK services in schools. However, administrative and non-comprehensive supervisory practices often fail to drive substantive improvement. Stufflebeam's CIPP (Context, Input, Process, Product) model offers a systemic evaluation framework, yet its application as a supervision model oriented toward sustainable service development remains underexplored. This study aims to synthesize empirical evidence on the CIPP model's application in evaluating school BK programs and analyze its potential to be developed into a supervision model that strengthens BK services. A systematic literature review (SLR) following the PRISMA protocol was conducted. Article searches were performed in SINTA, Google Scholar, Scopus, and DOAJ databases for the period 2015–2025, yielding nine relevant articles after final selection. Thematic analysis indicates that the CIPP model effectively evaluates BK programs comprehensively, identifying gaps in context (alignment of vision-mission with student needs), input (counselor qualifications, facilities), process (service implementation), and product (impact on student development). Key findings reveal that weaknesses in BK services often originate in the input aspect (resource limitations and non-standard counselor qualifications) and the process aspect (inadequate service time allocation). This study concludes that the CIPP model is not only useful as a summative evaluation tool but also holds strong potential as a formative supervision framework. Consequently, developing a CIPP-based supervision model can promote targeted, sustainable, and student-centered improvement of BK service quality in schools.